INTEREST IN ISLAM AND CROSS RELIGIONS - Muhammad Syauqi Bin-Armia (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2019)
The Islamic principle encourages people to be alert for society. To achieve the objective of sharia, Muslim has been provided the clear path to collaborate with the creatures fairly. The injustice financial practice one of the aspects that Islamic principles emphasise to not involve. On top of this, the usury (Riba) where someone charges the excess for the loan unfairly. The interest practice has been a critical topic throughout the time. Due to the unfair practice, the major religions and civilisations cursed this practice as general. Nevertheless, in practical situations, there were numbers of approaches for each religion and civilisation. Plato with among ancient philosopher criticized this and argued this is a media to squeeze poor people. In Judaism, the interest is prohibited among Jews, while in the Hinduism allowed otherwise in a lower caste in the society. In Christianity, priests in the medieval banned this practice, but it has been diluted in the 6th century due to the sovereign pressure. Islam sprightly prohibited the interest despite the diversity of its models, the value, the grade and to whom it will be exercised. This article emphasises on Islamic finance point of view towards the cross religions and civilisation. Utilised the library/literature-based research, the author delivers the main ideas in the comparative approaches of the interest issues. Abstrak: Prinsip Islam mendorong manusia agar waspada terhadap masyarakat. Untuk mencapai tujuan syariah, Muslim telah diberikan jalur yang jelas untuk bekerja sama dengan sesamanya secara adil. Praktik keuangan yang tidak adil merupakan salah satu aspek yang ditekankan agar di hindari oleh prinsip-prinsip Islam. Riba adalah praktik di mana seseorang membebankan kelebihan atas pinjaman secara tidak adil. Praktik bunga merupakan topik penting dari masa ke masa. Karena praktik ini tidak adil, agama-agama besar dan peradaban secara umum telah mengutuk praktik ini. Namun demikian, dalam situasi praktis, ada beberapa pendekatan dari setiap agama dan peradaban. Plato, kalangan filsuf kuno, mengkritik hal ini dan berpendapat bahwa praktik bunga adalah media untuk memeras orang-orang miskin. Dalam Yudaisme, bunga juga dilarang, sedangkan dalam Hinduisme, hal ini diizinkan kecuali untuk kasta yang lebih rendah di masyarakat. Dalam agama Kristen, para pendeta di abad pertengahan melarang praktik ini, tetapi praktik ini telah diizinkan pada abad ke-6 karena tekanan kedaulatan. Islam melarang praktik bunga terlepas dari apa pun modelnya, nilainya, kelasnya dan kepada siapa ia akan dilaksanakan. Artikel ini menekankan sudut pandang keuangan Islam terhadap lintas agama dan peradaban. Kata Kunci: Bunga, Riba, Peradaban